Metabolic activity of the sticker's lymphosarcoma - Rosa, Claudete Deguirmendjian [UNESP]; Rosa, Rubens [UNESP]; Rodrigues, Edson [UNESP]; Ocampos, Dario [UNESP]; Vuono, Laudinor de [UNESP]; Bacila, Metry [UNESP] (Elsevier B.V., 1987)
1. 1. Some parameters (glycolysis, respiration, levels of glycolytic enzymes) of the lymphoid cells from the Sticker's lymphosarcoma were established in order to better define the biochemical behavior of the venereal tumor of the dog. 2. 2. For comparative purposes lymphocytes from peripheral blood of normal tumor-bearing dogs were also studied. 3. 3. Lactic acid produced by the tumor cells during aerobic glycolysis is liberated in the reaction medium. 4. 4. Oxygen uptake is enhanced in the presence of succinate, but not with pyruvate, α-ketoglutarate, or malate as substrates. 5. 5. Higher levels of some of the enzymes from the glycolytic pathways as well as differences on the physicochemical and kinetic properties of the glycolytic regulatory enzymes are found in Sticker's tumor cells, when compared with the lymphocytes from peripheral blood of normal and tumor-bearing dogs. 6. 6. A fructose-bisphosphate positively modulated pyruvatekinase is found in the tumor cells. © 1987.
Keywords: Pyruvate kinase; Animal model; Cell respiration; Dog; Etiology; Glycolysis; Lymphatic system; Lymphosarcoma; Nonhuman; Animals; Dog Diseases; Dogs; Female; Glycolysis; Lactates; Lactic Acid; Lymphocytes; Lymphoma, Non-Hodgkin; Male; Oxygen Consumption; Pyruvate Kinase; Sexually Transmitted Diseases; Urogenital Neoplasms; Animalia; Canis familiaris